Synthesis and micromechanical properties of flexible, self-supporting polymer-SiO2 nanofilms - Vendamme, Richard (Langmuir : the ACS journal of surfaces and colloids, 2007)
Large-scale, self-supporting ultrathin films composed of an elastomeric polyacrylate network interpenetrated by a silica (SiO2) network were synthesized and characterized. The organic network was first photopolymerized and the silica structure was subsequently developed in situ in the preformed organic gel. Composition and morphology of the hybrid interpenetrated network (IPN) nanofilms were characterized by infrared spectroscopy, X-ray photoelectron spectroscopy, scanning electron microscopy, and transmission electron microscopy and compared with the case of zirconia (ZrO2) hybrid IPN reported earlier. Young modulus, ultimate tensile strength, and ultimate tensile elongation were determined for different organic/inorganic molar ratios and give some insights on how the composition of the nanofilms influence their robustness and self-supporting properties